Kedudukan Mantik Sebagai Mukadimah Ilmu: Satu Analisis Pandangan al-Imam al-Ghazzali - Hamat, Mohd Fauzi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2002)
This article tries to elaborate the position of logic in knowledge, especially in Islamic theoretical knowledge or wisdom from al-Ghazzali's point of view based on his book al-Mustasfa min 'llm al-Usul (the Quintenssence of the Principle of Islamic Jurisprudence). The texts which touch the issue and the brief explanation of logical discussion in his book are translated by the writer with anotation and then will be analysed and interpreted objectively.